Primer reporte de la colección de moluscos presentes en el Museo Maggiorino Borgatello (Punta Arenas, Chile) - Rosenfeld Sekulovic, Sebastián Alejandro; Marambio Gallardo, Johanna Valeska; Aldea Venegas, Cristian Leonardo (My University, 2016)
The Chilean mollusc collection of the Maggiorino Borgatello Salesian Museum (Punta Arenas, Chile) was created around the year 1905 aiming to preserve mollusc local knowledge. Since then until mid-twentieth century many specimens had been incorporated into the collection, which were identifi ed by local curators, but never underwent a comprehensive inventory and taxonomic identifi cation. This report provides comprehensive information on the taxonomy and distribution of mollusc species currently present in the museum. We recorded 37 species of molluscs (26 gastropods and 11 bivalves), of which 19 are commercially important species. From the biogeographical standpoint, the collection represents about 4% of the registered molluscs for the Chilean territory and about 10% of that reported for the Magellan Region. At the species level, we highlight the presence of specimens of Photinula roseolineata, Calliostoma irisans and Buccinanops paytensis, which have very few records in the Magellanic Biogeographic Province. The maintenance and preservation of this mollusc collection has great local and regional relevance as a way of preserving cultural heritage of this southern part of the world.
First report of the collection of molluscs present in the Maggiorino Borgatello Museum (Punta Arenas, Chile)
Keywords: magellan region; mollusca; museum; sub antarctic